Bright and photostable yellow fluorescent proteins for extended imaging - Jihwan Lee; Shujuan Lai; Shuyuan Yang; Shiqun Zhao; Francisco A. Blanco; Anne C. Lyons; Raquel Merino-Urteaga; John F. Ahrens; Nathan A. Nguyen; Haixin Liu; Zhuohe Liu; Gerard G. Lambert; et al. (Nature Communications)
Abstract Fluorescent proteins are indispensable molecular tools for visualizing biological structures and processes, but their limited photostability restricts the duration of dynamic imaging experiments. Yellow fluorescent proteins (YFPs), in particular, photobleach rapidly. Here, we introduce mGold2s and mGold2t, YFPs with up to 25-fold greater photostability than mVenus and mCitrine, two commonly used YFPs, while maintaining comparable brightness. These variants were identified using a high-throughput pooled single-cell platform, simultaneously screening for high brightness and photostability. Compared with our previous benchmark, mGold, the mGold2 variants display a ~4-fold increase in photostability without sacrificing brightness. mGold2s and mGold2t extend imaging durations across diverse modalities, including widefield, total internal reflection fluorescence (TIRF), super-resolution, single-molecule, and laser-scanning confocal microscopy. When incorporated into fluorescence resonance energy transfer (FRET)-based biosensors, the proposed YFPs enable more reliable, prolonged imaging of dynamic cellular processes. Overall, the enhanced photostability of mGold2s and mGold2t enables high-sensitivity imaging of subcellular structures and cellular activity over extended periods, broadening the scope and precision of biological imaging.